PENGARUH ESG SCORING TERHADAP HARGA SAHAM DENGAN MODERASI FAKTOR MAKROEKONOMI: STUDI PADA 30 PERUSAHAAN IDXESG LEADERS - Rizaldy, Rino; Endang Artiani, Listya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This study investigates the effect of ESG Scoring on stock prices of companies listed in the IDXESG Leaders index, incorporating inflation and interest rates as moderating variables. Using unbalanced panel data from 30 companies between 2020 and 2023, this study applies panel regression with the Fixed Effect Model (FEM) as the best fit. Moderated Regression Analysis (MRA) is used to examine the moderating role of macroeconomic factors. ESG Scoring has a significant negative effect on stock prices, suggesting that investors in Indonesia may still prioritize short-term profitability over sustainability. EPS has a positive influence, while PER and Free Float are not significant. Inflation strengthens the negative relationship between ESG and stock prices, while interest rates have no moderating effect. These results imply that ESG considerations are undervalued in volatile economic conditions, highlighting the need for improved investor awareness and stronger policy support for sustainable investing